Econometric Methods Aimed at Improving the Quality and Digitalization Of Educational Services (Eurasian Research Bulletin, 2022)
In this article, the main goal of education in the modern world is to prepare the future specialist for real life and work, to reveal his professional potential, to develop his qualities and abilities, including the need to contribute to the formation of powers for the use of econometric methods.